Interactive aspects of computer-mediated communication: "disagreement" in an English and a German public news group - Kleinke, Sonja (Discourses in interaction, 2010)
This study is placed in the context of current pragmatic research on public news group Internet communication as well as Watts’ notion of ‘emergent networks’ in the context of linguistic politeness. It investigates the functions and use of ‘disagreement’ in public news group Internet interaction in English and German. The paper starts with an analysis of the specific frame conditions holding in an English and a German discussion group including the development of ‘emergent networks’. Part two deals with the communicative functions of disagreement in the data and investigates their distribution, strategies of mitigation, preference organization, and communicative effects. Finally two closed discussion threads are analyzed in detail, with regard to their developing ‘emergent networks’ and their interactional effects.
Gesehen am 02.09.2019